DECODING THE SACRED: ARTIFICIAL INTELLIGENCE AND THE SYMBOLIC KNOWLEDGE STRUCTURES OF AFRICAN TRADITIONAL RELIGION - Moses Adeolu Agoi; Bukola Abosede Folaranmi; Zohaib Hassan Sain; Aulia Luqman Aziz; Shahzadi Hina Sain (Srawung: Journal of Social Sciences and Humanities, 2025)
African Traditional Religion (ATR) is based on symbolic systems that reflect cosmology, ethics, spirituality and social order, which are represented through divination, rituals, proverbs, sacred objects as well as texts such as Yoruba Ifa verses. Scholars nowadays focus not only on their multivocal character but also on their epistemic and moral functions: symbols act as organs of knowledge no less than objects of cultural artefacts. AI tools, by symbolically representing that knowledge, through ontologies and explainable learning, provide means to decode, and maintain such sacred systems cultural sensitively. Indicatively, the article Preserving Indigenous Knowledge: Leveraging Digital Technology and Artificial Intelligence describes the way interactive platforms and AI-based applications preserve indigenous knowledge, without violating cultural guidelines and intellectual property rights. Using Classical Machine Learning and Deep Learning, Adinkra Symbol Recognition in Ghana was highly accurate in classifying Adinkra symbols. The results of the studies indicate that AI can improve preservation, access, and learning; however, it is unable to reproduce spiritual intention and group validation. Such ethical concerns as reductionism, digital colonialism, and cultural ownership are not new to the recent literature. This paper thus suggests an alternative approach in which AI would be used to supplement AIR custodianship to make sure that the knowledge is not stale, but dynamic, secure, and useful in the digital era.